Farm family effects of adopting improved and hybrid sorghum seed in the Sudan Savanna of West Africa. (January 2018) - Smale, Melinda; Assima, Amidou; Kergna, Alpha; Thériault, Véronique; Weltzien, Eva
Highlights: The first sorghum hybrids based on local germplasm in West Africa yield well on farms. Intrahousehold status on extended family farms affects adoption of improved seed. Adoption raises yield, reduces the harvest share consumed and also purchased. Adoption increases the harvest share sold and dietary diversity. Abstract: Uptake of improved sorghum varieties in the Sudan Savanna of West Africa has been limited, despite the economic importance of the crop and long-term investments in sorghum improvement. One reason why is that attaining substantial yield advantages has been difficult in this harsh, heterogeneous growing environment. Release in Mali of the first sorghum hybrids in Sub-Saharan Africa that have been developed primarily from local germplasm has the potential to change this situation. Utilizing plot data collected in Mali, we explain the adoption of improved seed with an ordered logit model and apply a multivalued treatment effects model to measure impacts on farm families, differentiating between improved varieties and hybrids. Since farm families both consume and sell their sorghum, we consider effects on consumption patterns as well as productivity. Status within the household, conferred by gender combined with marital status, generation, and education, is strongly related to the improvement status of sorghum seed planted in these extended family households. Effects of hybrid use on yields are large, widening the range of food items consumed, reducing the share of sorghum in food purchases, and contributing to a greater share of the sorghum harvest sold. Use of improved seed appears to be associated with a shift toward consumption of other cereals, and also to greater sales shares. Findings support on-farm research concerning yield advantages, also suggesting that the use of well-adapted sorghum hybrids could contribute to diet diversification and the crop's commercialization by smallholders.